ASUHAN KEPERAWATAN PADA TN. N DENGAN TUBERCULOSIS DENGAN MASALAH BERSIHAN JALAN NAFAS TIDAK EFEKTIF DI WILAYAH GEBANG RAYA KOTA TANGERANG - Valvi Oktiviyani, (2023)
The purpose of this study is to assess the client's condition, analyze the data that has been collected, determine nursing diagnoses, plan actions to be taken, carry out these actions, evaluate, and document the entire process that has been carried out. The research method used in this research is qualitative with a case study approach. The results of this study are in the planning and implementation of nursing actions, there are no gaps between theory and reference books. In nursing evaluation, three nursing diagnoses were resolved properly and positive outcome criteria were met. So it can be concluded that the nursing care given to the client Mr. N is effective and in accordance with the theory and book. Mr. N is effective and in accordance with the theory and reference books used. This shows that the author has conducted a careful nursing assessment and applied relevant theories to determine accurate nursing diagnoses. In addition, the author also managed to plan and implement nursing interventions in accordance with the diagnosis set, and successfully evaluated the results of these interventions. Mr. Client. Mr. N also seemed to respond positively to the nursing actions provided, so it can be concluded that the nursing care provided has provided great benefits to the client.